Entwicklungstendenzen und zukunftsperspektiven neuer medien in der bildung - Blakowski, Gerold (Journal of Business Economics and Management, 2003)
The usage of new media and learning types is a complex and dynamic field. Simple statements concerning the potential, efficiency and effectiveness of E‐Learning are often based on wrong and undifferentiated premises. These statements are discussed with regard to the different types of E‐Learning. It is pointed out that there is a need for communication and cooperation as it is supported in Tele‐Tutoring and Computer Supported Cooperative Learning. By using these types of learning in combination with blended learning, the full potential of learning with new media can be tapped. Article in German. First Published Online: 14 Oct 2010